MENINGKATKAN KUALITAS PEMBELAJARAN ABAD KE-21: EVALUASI PELATIHAN DEEP LEARNING BAGI GURU DI BANDAR LAMPUNG - Bambang Riadi; Yanuar Dwi Prastyo; Aditya Pratama (Education, Language, and Arts: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to enhance teachers’ competencies in understanding and implementing the Deep Learning approach in meaningful learning. The training was conducted on October 3, 2025, at Hall B of the Faculty of Teacher Training and Education, Universitas Lampung, and involved 20 teachers from various senior high schools in Bandar Lampung. The training employed a participatory workshop approach encompassing conceptual presentations, instructional material development workshops, microteaching sessions, and reflective activities. Data were collected through observations, post-test assessments, and interviews. The evaluation results showed that 80% of the participants answered all post-test items correctly, 15% answered nine items correctly, and 5% answered eight items correctly. These findings indicate a significant improvement in teachers’ understanding of Deep Learning strategies and their readiness to implement meaningful learning in accordance with the demands of the Merdeka Curriculum. In addition, the training strengthened teachers’ professional awareness in facilitating reflective, contextual, and learner-centered instruction oriented toward the development of 21st-century competencies.   Kegiatan pengabdian kepada masyarakat ini bertujuan meningkatkan kompetensi guru dalam memahami dan menerapkan pendekatan Deep Learning dalam pembelajaran bermakna. Pelatihan dilaksanakan pada 3 Oktober 2025 di Aula B FKIP Universitas Lampung, melibatkan 20 guru dari berbagai SMA di Bandar Lampung. Metode pelatihan menggunakan pendekatan workshop-partisipatif yang meliputi pemaparan konsep, lokakarya penyusunan perangkat ajar, microteaching, dan refleksi. Data diperoleh melalui observasi, post-test, dan wawancara. Hasil evaluasi menunjukkan bahwa 80% peserta menjawab benar seluruh soal post-test, 15% menjawab benar sembilan soal, dan 5% menjawab benar delapan soal. Temuan ini menegaskan peningkatan signifikan pemahaman guru terhadap strategi Deep Learning serta kesiapannya menerapkan pembelajaran bermakna sesuai tuntutan Kurikulum Merdeka. Pelatihan juga memperkuat kesadaran profesional guru dalam menghadirkan pembelajaran yang reflektif, kontekstual, dan berorientasi pada pengembangan kompetensi abad ke-21.